Three Classical Methods to find the Cube Roots: A Connective Perspective on Lilavati, Vedic and Pande’s Procedures - Parajuli, Krishna Kanta (Journal of Nepal Mathematical Society, 2021)
South Asian region has made a glorious history of mathematics. This area is considered as fer- tile land for the birth of pioneer mathematicians who developed various mathematical ideas and creations. Among them, three innovative personalities are Bhaskaracarya, Gopal Pande and Bharati Krishna Tirthaji and their specific methods to find cube root are mainly focused on this study. The article is trying to explore the comparative study among the procedures they adopt. Gopal Pande disagrees with the Bhaskaracarya’s verse. He used the unitary method against that method mentioned in Bhaskaracarya’s famous book Lilavati to prove his procedures. However, the Vedic method by Tirthaji was not influenced by the other two except for minor cases. In the case of practicality and simplicity, the Vedic method is more practical and simpler to understand for all mathematical learners and teachers in comparison to the other two methods.